Kinerja ESG pada stock liquidty dengan kepemilikan keluarga sebagai variable moderasi - Ali Firdaus; Cynthia Afriani Utama (Department of Accounting, Faculty of Economics and Business, Universitas Pembangunan Nasional Veteran Jakarta, 2025)
This study explores the extent to which family ownership moderates the linkage between ESG performance and stock liquidity. A purposive sampling strategy, categorized under non-probability sampling methods, was adopted in this study to ensure the selection of samples aligned with the research objective. The sample consists of 45 companies, yielding 225 firm-year observations over the 2019–2023 period. The data were obtained from Thomson Reuters and manually from each company’s annual reports. The empirical results reveal that Environmental, Social, and Governance (ESG) performance does not have a statistically significant impact on stock liquidity within the Indonesian market. Additionally, family ownership, as a moderating variable, does not demonstrate a significant moderating effect neither attenuating nor amplifying the relationship between ESG performance and stock liquidity. This study contributes to addressing the gap in the literature regarding the interaction between ESG performance and family ownership in relation to stock liquidity in emerging markets. This study offers significant practical implications for various stakeholders, including regulators, listed firms, and investors in their decision-making processes. The number of companies meeting this criterion is limited, which restricts the generalizability of the findings to all firms in Indonesia. Keywords: ESG Performance; Stock Liquidity; Family Ownership; Indonesia.